Testing a parent support intervention to improve success of first year students at a historically-Black University (HBCU) - Sharron Xuanren Wang; Lawita Cheatham-Hemphill; Melissa A. Harrington (Frontiers in Education)
Intergenerational education mobility is one of the key dimensions of social mobility. Educational mobility is defined as the association between parents and children’s educational attainment. Children born to parents with a college degree are more likely to graduate from college. On the other hand, first generation college students (i.e., students who have parents without a college degree) are less likely to go to college and are more likely to drop out of college compared to students with college-educated parents. Previous literature has suggested that parental involvement in higher education leads to improved student performance. Parents who did not attend college, on the other hand, might not have the knowledge to help their children navigate college. College students, especially in their freshman year, face many challenges, such as a heavier workload than is typical for high school and a distracting peer culture. At our Historically Black University, we developed a year-long communication plan targeted at parents of first-year students and aimed at boosting the educational cultural capital of parents and cultivating a supportive environment to enhance students’ educational experiences and outcomes. One of our main goals was to help retain students in the academic pipeline in majors related to Science, Technology, Engineering and Mathematics (STEM), as well as the health sciences, while also motivating students to pursue graduate school or obtain a job in the field. The program has graduated 3 cohorts of parents of first year students. Applying a mixed method approach, including an online survey method and in-depth qualitative interviews, our results indicated that parents in the Parent University program benefited from the information acquired. Details about the intervention, the implications of our findings, and the lessons learned from program implementation are discussed.